Therapeutic and medicinal uses of lycopene: a systematic review - Joshi, Bishal; Kar, Sanjit Kumar; Yadav, Prem Kumar; Yadav, Shankar; Shrestha, Laxmi; Bera, Tushar Kanti (International Journal of Research in Medical Sciences, 2020)
Lycopene is a carotenoid present in fruits and vegetables. The richest sources of lycopene are tomatoes and tomato products. The beneficial effects of lycopene in human health and disease are mainly associated with its antioxidant properties. Lycopene is a carotenoid with strongest antioxidant property because of its capability of quenching the singlet oxygen. Eleven conjugated double bonds of lycopene give it a deep red color and are responsible for its antioxidant activity which is major functional feature of lycopene. Dietary intakes of tomatoes and tomato products containing lycopene have been shown to be associated with decreased risk of chronic diseases such as cancer and cardiovascular diseases in numerous studies. Although there are evidences from many epidemiological and cell culture and animal studies explaining the inverse relationship between lycopene and cancer or cardiovascular disease risk, more clinical trial data is needed to support this hypothesis. In this article we outline the possible mechanisms of action of lycopene and review the current understanding of its role in human health and disease prevention.